Preparedness Study of Ketaping Beach Tourism Object Visitors Against Earthquake and Tsunami Disasters in Padang Pariaman Regency (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
West Sumatra has promising tourism potential because it has the potential for natural beauty, cultural and culinary attractions. One of them is Padang Pariaman Regency which has seven beach and island tourist attractions. Besides having tourism potential, West Sumatra Province also has a very high potential disaster risk. Padang Pariaman Regency has a very high level of tsunami disaster risk. The fact that the potential risk of tsunami disaster is very high and the potential for beach tourism is also high can hamper and disrupt the lives and livelihoods of the community. The purpose of the study was to determine the level of preparedness of visitors in facing a tsunami disaster along the coast, in this case the research locus was Panjang Beach Nagari Ketaping. This research method is descriptive quantitative with purposive sampling calculation technique using tourism object visitor preparedness index analysis which consists of four parameters which include knowledge and attitude factors, emergency response plans, warning systems, and resource mobilization. The results showed that the level of preparedness of visitors to Ketaping Beach tourism objects against earthquake and tsunami disasters was dominated by the level of preparedness "less prepared" with a percentage of 42%. While the smallest is the "very prepared" preparedness category with a percentage of 2%. Thus it can be concluded that there are still many visitors to Ketaping Beach tourism objects who have not prepared themselves for earthquake and tsunami disasters that can occur at any time. So that visitors to the Ketaping Beach tourist attraction are expected to make mitigation efforts both actively and passively by increasing capacity independently such as training and disaster socialization and already knowing information on the level of risk of earthquakes and tsunamis at the location of the tourist attraction they will visit.